Bungalow 2 - Steel, Danielle (New York : Delacorte Press, 2007)
When Marin County mother and freelance writer Tanya Harris gets the chance to write a major Hollywood screenplay, she finds herself thrust into an unfamiliar world that forces her to reconcile her two lives as a suburban mom and award-winning screenwriter.